IMPLEMENTASI METODE MARKET BASKET ANALYSIS (MBA) PADA APLIKASI E-COMMERCE STUDI KASUS ANANDA SHOP - Saraswati, Rita; Hijriani, Astria; Febriansyah, Febi Eka (Universitas Lampung, 2016)
This research is designing The Implementation of Market Basket Analysis (MBA) Method on E-Commerce Application as one way to expand and help the selling on Ananda shop.Â In this Implementation, Market Basket Analysis Method (MBA) was used to determine which product will be bought by customers in one time through analysis of customersâ€™ transaction list. This E-Commerce Application gives suggestion on related product match to product that has been chosen by a customer, so customer can easily see the product and bought it. This system was built using PHP and MySQL language. The result of functional data testing based on test case showed that this system can work â€œproperlyâ€ to its purpose.